Enhanced Antiviral Ability by a Combination of Zidovudine and Short Hairpin RNA Targeting Avian Leukosis Virus - Wang, Qun; Su, Qi; Liu, Bowen; Li, Yan; Sun, Wanli; Liu, Yanxue; Xue, Ruyu; Chang, Shuang; Wang, Yixin; Zhao, Peng (Frontiers in Microbiology, 2022)
Avian leukosis virus (ALV) causes tumor diseases in poultry and is circulating in all over the world, leading to significant economic losses. Also, mixed infection of ALV with other viruses is very common and is often reported to contaminate live vaccines. At present, there is no effective method to suppress the replication of ALV in vitro, so it is very difficult to remove it in mixed infection. As a retrovirus, the replication of ALV can be limited by reverse transcriptase (RT) inhibitors like Zidovudine (AZT), but it also causes non-targeted cytotoxicity. In order to find the optimal solution in cytotoxicity and inhibition efficiency in vitro culture system, we firstly designed a combination therapy of AZT and shRNA targeting ALV, and then verified its efficiency by multiple biological methods. Results showed that shRNA can effectively inhibit the expression of RT, and then limit the replication of ALV. The combination of AZT and shRNA can significantly improve the antiviral efficiency in viral replication, shedding and provirus assembly under the condition of low cytotoxicity. Overall, in this study, the combination therapy of AZT and shRNA targeting ALV showed excellent antiviral performance against ALV in vitro culture system. This method can be applied to multiple scenarios, such as the removal of ALV in mixed infection or the purification of contaminated vaccine strains.